(untitled) (Journal of Patan Academy of Health Sciences, 2018)
Introductions: A rupture of the Anterior Cruciate Ligament (ACL) is the most common ligament injury resulting in instability of the knee which can cause secondary articular injury and early osteoarthritis (OA). Aim of this study was to evaluate the short term outcomes of ACL reconstruction using Bone Patellar Tendon Bone Auto Graft (BPTB) auto graft and factors that might contribute to poor results. Methods: Patients with Anterior Cruciate Ligament injury during the period of July 2013 to May 2014 were enrolled to observe the outcome of the ACL reconstruction using BPTB without arthroscopy. Lysholm Knee Scoring Scale was used to determine the clinical outcome. Outcome parameters were evaluated using Statistical Package for Social Science Version 20 (SPSS). Results: Total 30 normal or near normal function outcome of knee was reported in 29 (97%) patients after ACL reconstruction using BPTB without arthroscopy. There was no failure of grafts. Good static knee stability achieved with increased patient’s satisfaction. Lysholm Score was excellent in 27 (90%) and good in 3 (10 %) cases. Anterior knee pain persisted in 6 cases (20%). Conclusions: Excellent functional outcome with BPTB auto graft in Anterior Cruciate Ligament injury was achieved.